(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2002)
An exact estimate is given for the modulus of smoothness in weighted Orlicz sequence spaces and the best order of LH^ω-smoothness of bump functions is found for α ≤ 2.